2011
DOI: 10.1002/aqc.1244
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses of harbour seals to human‐induced disturbances

Abstract: ABSTRACT1. In Denmark, harbour seals, Phoca vitulina, were first protected in 1977, and since then a number of seal reserves have been established in Danish waters. The effectiveness of these reserves to prevent human-induced disturbances to the seal population have, however, not been evaluated.2. To evaluate this, experimental disturbances were conducted in one of the most important seal reserves in Denmark (Anholt seal reserve). Specifically, the behavioural responses (alert distance, flight initiation dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 39 publications
1
39
1
Order By: Relevance
“…It might be more useful to focus attention on boating practices. The nature of a boat's approach has been shown to affect the response of harbour seals (Allen et al 1984, Suryan & Harvey 1999, Andersen et al 2012. Our observations during the present study confirmed that in some cases seals entered the water due to backwash from the boat or to boat operation (stopping and changing direction).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It might be more useful to focus attention on boating practices. The nature of a boat's approach has been shown to affect the response of harbour seals (Allen et al 1984, Suryan & Harvey 1999, Andersen et al 2012. Our observations during the present study confirmed that in some cases seals entered the water due to backwash from the boat or to boat operation (stopping and changing direction).…”
Section: Discussionsupporting
confidence: 84%
“…Some studies (e.g. Andersen et al 2012), however, have reported greater response distances in harbour seals.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Kastelein et al (2006) in a similar experiment with different types of sound stimuli found that the same 2 seal species did not habituate; however, here the seals were not fed. Harbour seals fled a shorter distance when disturbed by people during the breeding season compared to before and after the breeding season (Andersen et al 2012). For wild porpoises, for example at our study site, some individuals may tolerate pinger signals better than others due to motivational differences, such as hunger.…”
Section: Gradual Lessening Of Response To Pinger Signalsmentioning
confidence: 99%
“…, Andersen et al . ), the extent of previous exposure to human presence (Yorio and Boersma , Boren et al . , Holcomb et al .…”
mentioning
confidence: 99%
“…The knowledge and evaluation of these factors is fundamental for the creation of management and conservation strategies for this type of species (Andersen et al . ).…”
mentioning
confidence: 99%